A Nodule-Specific Lipid Transfer Protein AsE246 Participates in Transport of Plant-Synthesized Lipids to Symbiosome Membrane and Is Essential for Nodule Organogenesis in Chinese Milk Vetch. Issue 2 (23rd December 2013) - Lei, Lei; Chen, Ling; Shi, Xiaofeng; Li, Yixing; Wang, Jianyun; Chen, Dasong; Xie, Fuli; Li, Youguo
Abstract : A nodule-specific lipid transfer protein contributes to transport to the symbiosome membrane and is required for effective legumerhizobium symbiosis . Abstract: Rhizobia in legume root nodules fix nitrogen in symbiosomes, organelle-like structures in which a membrane from the host plant surrounds the symbiotic bacteria. However, the components that transport plant-synthesized lipids to the symbiosome membrane remain unknown. This study identified and functionally characterized the Chinese milk vetch ( Astragalus sinicus ) lipid transfer protein AsE246, which is specifically expressed in nodules. It was found that AsE246 can bind lipids in vitro. More importantly, AsE246 can bind the plant-synthesized membrane lipid digalactosyldiacylglycerol in vivo. Immunofluorescence and immunoelectron microscopy showed that AsE246 and digalactosyldiacylglycerol localize in the symbiosome membrane and are present in infection threads. Overexpression of AsE246 resulted in increased nodule numbers; knockdown of AsE246 resulted in reduced nodule numbers, decreased lipids contents in nodules, diminished nitrogen fixation activity, and abnormal development of symbiosomes. AsE246 knockdown also resulted in fewer infection threads, nodule primordia, and nodules, while AsE246 overexpression resulted in more infection threads and nodule primordia, suggesting that AsE246 affects nodule organogenesis associated with infection thread formation. Taken together, these results indicate that AsE246 contributes to lipids transport to the symbiosome membrane, and this transport is required for effective legume-rhizobium symbiosis.